Implantação endoscópica de stent metálico autoexpansível (E-SEMS) versus terapia endoscópica a vácuo (TEV) para tratamento de perfurações esofágicas traumáticas: um estudo randomizado - Oliveira, Alessandrino Terceiro de (2023)
Endoscopic implantation of a self-expanding metallic stent (E-SEMS) versus endoscopic vacuum therapy (EVT) for the clinical treatment of traumatic esophageal perforations: a randomized trial. ALESSANDRINO TERCEIRO DE OLIVEIRA. Postgraduate Stricto Sensu of Department of Surgery, School of Medicine, Federal University of Ceará (Doctor Degree in Medical-Surgical Sciences). July 2023. Advisor. Prof. Dr Paulo Roberto Cavalcante de Vasconcelos Introduction. Esophageal injuries are transmural ruptures of the esophagus that subsequently lead to leakage of intraluminal contents into the surrounding mediastinum. This causes local inflammation, a systemic inflammatory response, and eventually the development of sepsis that results in significant morbidity and mortality. This study aimed to compare endoscopic stent implantation with self-expandable metallic stent (E-SEMS) or endoscopic vacuum therapy (EVT) in the treatment of esophageal perforations. Patients and method. The study randomly evaluated 30 patients with traumatic esophageal perforations. The two groups (E-SEMS and EVT) of patients were assessed for duration of treatment, length of stay, clinical outcomes, and treatment success. Results. Age (mean±SD) was 48.06±17.80 and 44.63±27.51 for patients in the E-SEMS and EVT groups, respectively. In both groups, the most common cause of injury was a foreign body 63.3% (19/30), followed by gunshot wounds 30.0% (9/30) and stab wounds 6.7% (2/30). The (mean±SD) treatment duration for E-SEMS (45.8±12.9 days) was significantly greater than EVT (24.42±13.21 days) (p<0.0001). In addition, the E-SEMS group demonstrated a significantly shorter hospital staycompared to the EVT group (p=0.0209). Evaluating the clinical results E-SEMS demonstrated 93.75% (15/16) discharge percentage compared to EVT which showed 71.4% (10/14). Deaths occurred in the E-SEMS and EVT with 6.3% (01/16) and 28.6% (04/14) frequencies, respectively (p=0.1571). Furthermore, treatment success showed no significant difference between E-SEMS 93.7% (15/16), 6.3% (01/16) and EVT 78.6% (11/14), 21.4 % (03/14) successful and unsuccessful respectively (p=0.3155). Four of the five deaths were caused by sepsis in patients undergoing the EVT procedure, and one patient in the E-SEMS group died of heart failure unrelated to the study. The hospital costs (mean±SD) were calculated at 19,266.08±10,925.00 reais and 38,453.17±23,840.40 reais for the placement of the self-expandable metallic stent and endoscopic vacuum therapy, respectively Conclusions. Endoscopic implantation with a self-expanding metallic stent showed a shorter hospital stay, but a longer duration of treatment compared to endoscopic vacuum therapy. Both therapies showed no significant difference in clinical outcome. The therapy with endoscopic insertion of esophageal stent had lower hospital costs for patient for SUS than endoscopy vacuum therapy.